Analisis Kebutuhan Finansial berbasis Green Economy pada Rumah Tangga - Astuti, Ratna Fitri; Permatasari, Indah; Arliyanti, Shila Putri; Manurung, Eris (Universitas Mataram, 2025)
The achievement of family financial needs can be started from how to use household production factors to be effective and efficient. Households must be able to apply self-control in order to suppress the exploitation of natural resources to meet endless needs and desires. The study was conducted to examine in depth the application of green economy as a supporter of achieving financial needs. The study was conducted on households in the city of Samarinda with a marriage age of ≥ 10 years, and households have a monthly income of ≥ Rp. 5,000,000. The sample used in the study was 96 respondents calculated using the lemeshow formula. Data collected through the distribution of questionnaires were subjected to descriptive analysis to describe and explain in depth several indicators. Based on the results of the study, it was found that 74 households or 77.08% of the total respondents were categorized as having a very high or strong desire to encourage and implement environmentally friendly economic activities with the aim of achieving financial needs. Households have an understanding of the importance of achieving financial needs. These activities are achieved through actions that are not only carried out selfishly by excessively consuming resources, but are also balanced with actions based on the green economy.